RECONSTRUCTION PROVISIONS ON COORDINATION BETWEEN INTELIGENCE AGENCIES TO IMPROVE NATIONAL SECURITY IN INDONESIA - Jupri Nababan; Rr. Catharina Dewi Wulansari (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study discusses the reconstruction of regulations regarding coordination among intelligence agencies to enhance national security in Indonesia. The primary focus is on the dual authority between the State Intelligence Agency (Badan Intelijen Negara, BIN) and the Police Intelligence and Security Agency (Baintelkam) following the enactment of Law No. 17 of 2011 on State Intelligence. The research approach used in this thesis is normative juridical with a multidisciplinary approach that combines the disciplines of law and management. The findings indicate that overlapping authority and the lack of an integrated information-sharing mechanism lead to policy fragmentation and delayed responses to national security threats. The study’s main recommendation is to revise Law No. 2 of 2002 on the Indonesian National Police to align the strategic role of BIN with the operational duties of Baintelkam. Furthermore, clear implementing regulations are needed to establish coordination and information-sharing mechanisms, ensuring an effective, efficient, and integrated intelligence system to address increasingly complex threats in Indonesia.